Evaluation of the Goals and Objects of Assessment of Aspects of Student Learning through Bloom’s Taxonomy - Muhammad Rizwan Ilhami (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
This research aims to determine student performance at the very difficult basic education level. Education in the modern era requires a lot of evaluation that focuses on research targets and objects. One of them can be viewed from the aspects in Bloom’s Taxonomy. Bloom’s Taxonomy is a technique developed by Benjamin Bloom in 1956. This research uses descriptive qualitative research methods. The results of this study indicate that student assessment is an important part of education and is carried out through the examination process and that test question paper readiness has reliably involved schemes. Bloom’s Taxonomy consists of three progressive models that are used to group instructive learning objectives into dimensions of multifaceted and explicit nature. Lists of cognitive domains have been the primary focus of much of traditional education and are often used to structure curriculum learning objectives, assessments and activities. Bloom’s Taxonomy is a tool that can help human services educators broaden the depth of their students’ learning. There are four classifications of learning worth noting: verifiable, applied, procedural, and meta cognitive.